PWE-137 The role of 99mtechnetium-labelled hepato imino diacetic acid (HIDA) in the management of biliary pain. (28th May 2012) - Dave, R; Cockbain, A; Toogood, G
Abstract : Introduction: Biliary pain is a common presentation in the acute surgical take and the surgical clinic. In patients with normal ultrasound findings, symptoms can sometimes be disregarded as being non-specific. We propose that in this cohort, a HIDA scan is a useful investigation, and patients with a positive test have good results following cholecystectomy. Methods: We obtained reports of all HIDA scans with an abnormal ejection fraction (EF <40%) performed in our centre from 15 May 2007 to 28 December 2010. This database was cross-linked with a prospectively-maintained database and electronic records of patients undergoing cholecystectomy in the same period. All patients with a positive HIDA who went on to have laparoscopic cholecystectomy (LC) were followed-up by a review of the electronic records, and a telephone interview to asses symptom improvement. Results: 50 patients were investigated. Mean age was 48, and majority were female. Ultrasound findings revealed no stone disease and normal gall bladder in 96%. 92% of patients were happy with the decision to proceed with LC, and 87.5% felt that their symptoms were improved (62.5% "Very Much Improved"). Post-operatively, 56.3% had no residual pain whatsoever and 31.3% had only occasional mild discomfort. The histology was pathological in 83%; 29% had stones in the gall bladder. During the HIDA scan, injection of a CCK-analogue caused pain in 56%. Symptoms were "Very Much Improved" after LC in 74% and 44% respectively in the responders and non-responders to CCK-analogue injection. The sensitivity of CCK-analogue injection was 68% and specificity was 50%. Conclusion: HIDA scan is a useful clinical tool in the diagnosis and management of patients with typical biliary pain and normal ultrasound. Outcomes following LC in this cohort of patients are favourable, with high patient satisfaction. The injection of a CCK analogue is a sensitive adjunct to the test, but non-response does not rule out benefit from LC. Competing interests: None declared.